Masked trichothecene and zearalenone mycotoxins withstand digestion and absorption in the upper GI tract but are efficiently hydrolyzed by human gut microbiota in vitro. Issue 4 (6th February 2017) - Gratz, Silvia W.; Dinesh, Reshma; Yoshinari, Tomoya; Holtrop, Grietje; Richardson, Anthony J.; Duncan, Gary; MacDonald, Susan; Lloyd, Antony; Tarbin, Jonathan
Abstract : Masked trichothecenes and zearalenone compounds are stable in the small intestine. In the large intestine the resident microbiota efficiently release free trichothecenes within 24 h, whereas zearalenone compounds are released and further metabolised. Toxicity of these metabolites remains unknown. Abstract : Scope: Cereal grains are commonly contaminated with Fusarium mycotoxins and their plant‐derived masked metabolites. The fate of masked mycotoxins in the human gut is poorly understood. Here we assess the metabolism and transport of glucoside metabolites of common trichothecenes (deoxynivalenol, nivalenol, T‐2 toxin) and zearalenone compounds (zearalenone, α‐ and β‐zearalenol) in the human gut in vitro. Methods and results: Masked mycotoxins were incubated with artificial digestive juices and absorption was assessed in differentiated Caco‐2/TC7 cells. Colonic metabolism was studied using fecal batch cultures from five donors and mycotoxins were detected using LC‐MS/MS. All masked mycotoxins were stable under upper GI tract conditions and no absorption was observed. Free trichothecenes were absorbed intact whereas free zearalenone compounds were absorbed and metabolized to undetected compounds by Caco‐2/TC7 cells. Human gut microbiota efficiently hydrolyzed all masked mycotoxins. Trichothecenes were fully recovered as parent mycotoxins whereas 40–70% of zearalenone compounds were further metabolized to unknown metabolites. Conclusion: Our results demonstrate that masked trichothecenes will reach the colon intact to be released as parent mycotoxins by gut microbiota, hence contributing to mycotoxin exposure. Masked zearalenone compounds are metabolized by gut microbiota and epithelial cells and the identity and toxicity of metabolites remain to be determined.